Process of preparing regioregular polymers - Heeney,M; Zhang,W; Duffy,W; Mcculloch,I; Koller,G (2007)
The invention relates to a process of prepg. regioregular polymers, in particular head-to-tail (HT) poly-(3-substituted) thiophenes with high regioreguiarity, to novel polymers prepd. by this process, to the use of the novel polymers as semiconductors or charge transport materials in optical, electrooptical, or electronic devices including field effect transistors (FETs), electroluminescent, photovoltaic, and sensor devices, and to FETs and other semiconducting components or materials comprising the novel polymers.